A novel dicyanisophorone-based colorimetric and ratiometric fluorescent probe for the detection of hypochlorite in the environment and living cells. (December 2022) - Liu, Li; Yang, Yixian; Cui, Yuanyuan; Zhu, Weiju; Fang, Min; Li, Cun
Abstract: A novel dual emissive fluorescent probe SFQ was designed and synthesized by linking dicyanisophorone and thiophene aldehyde units to carbazole groups. The probe SFQ has high selectivity and sensitivity toward ClO − . Upon addition of ClO − to the solution of probe SFQ resulted in a noticeable color changed from orange to pink under natural light. Meanwhile, SFQ could make a ratiometric fluorescence response to ClO − at two different excitation wavelengths, with the change of color from orange-red fluorescence to cyan fluorescence under the 365 nm UV lamp. The detection limit was 1.4 × 10 −7  mol/L under ratiometric conditions. The study on the reaction mechanism showed that when SFQ reacted with ClO −, the cyano group disappeared and the cyclic ketone SFQ -O came into being. Furthermore, probe SFQ was successfully used to monitor ClO − in HepG2 cells and detect ClO − in actual environmental water samples. Graphical abstract: Image 1 Highlights: A novel probe SFQ for colorimetric and ratiometric identification of ClO − was prepared. SFQ can respond instantly to ClO − (<5 s) and has a large Stokes shift (145 nm). SFQ was successfully used to monitor ClO − in HepG2 cells and detect ClO − in actual environmental water samples.